Complete seizure freedom is possible in patients with MTLE-HS after surgery in spite of extratemporal electro-clinical features - TOYDEMIR, Hulya Ertasoglu; Ozkara, Cigdem; Uysal, Omer; UYSAL, ÖMER; Ozyurt, Emin; Uzan, Mustafa (My University, 2015)
Purpose: The aim was to identify the common typical and atypical ictal semiologic and EEG features of patients with mesial temporal lobe epilepsy and hippocampal sclerosis who became seizure-free postoperatively.